ANALISA KEGIATAN BINA SISWADALAM MEMBENTUK KARAKTER SISWA KELAS VII DI MTS TAJHIZ DINIYAH MESKOM - Diana, Rahma; Sofiani, Ika Kurnia (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research is motivated by several symptoms of the problem encountered bz researchers, namely there are still manz student who do not follow school rules  and there are still many studens behavior that is not polite to the teacher in class such as not wanting to listen to what the teacher explains, there are some students who chat with peers when the teacher explains, there are some students who wear make up at school, there are some students who fight wits classmates during class hours, and skip school when no teacher is in the local area, then there are some students who smoke outside the school environment using school uniforms. The purpose of this research is to find out how student developmen activities shape student character. The theory in this study is the activity of fostering student and forming student character. There is also this type of research is qualitative with a descriptive approach. The research instrument are observation guidelines and interview guidelines. Data collection uses observation, interviews, and documentation. Procesing and analysis of data used in this study are data collection, data reduction, data presentation, and conclusions. The result this study based on the result of the interview were that student develpment activities were able to shape the character of MTs Tajhiz Diniyah Meskom